2015
DOI: 10.1007/s40279-015-0318-7
|View full text |Cite
|
Sign up to set email alerts
|

Black and White Race Differences in Aerobic Capacity, Muscle Fiber Type, and Their Influence on Metabolic Processes

Abstract: Obesity is a known risk factor for cardiometabolic disease. Increasing aerobic capacity (VO2max) reduces adiposity, maintains weight, and reduces the risk of developing obesity and cardiometabolic disease. Two major determinants of aerobic capacity are the metabolic properties specific to a particular muscle fiber type and the capacity of the cardiorespiratory system to deliver nutrient-rich content to the muscle. Recent research suggests that some race/ethnic groups, particularly non-Hispanic Black subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 48 publications
(101 reference statements)
2
42
1
3
Order By: Relevance
“…Another mechanism that could contribute to lower S i and compromised glucose control, is a higher percentage of Type II skeletal muscle fibers that can be found among NHBs compared with NHWs. Previous research contrasting race–ethnic groups has suggested a potential predisposition to an increased risk for T2D with a higher percentage of Type II fibers . More specifically, among lean, obese or T2D participants, Type I fibers have been shown to have higher expression of the glucose transporter GLUT4, a greater insulin‐stimulated glucose disposal rate, higher glucose oxidation rates, and higher non‐oxidative glucose metabolism compared with Type II fibers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism that could contribute to lower S i and compromised glucose control, is a higher percentage of Type II skeletal muscle fibers that can be found among NHBs compared with NHWs. Previous research contrasting race–ethnic groups has suggested a potential predisposition to an increased risk for T2D with a higher percentage of Type II fibers . More specifically, among lean, obese or T2D participants, Type I fibers have been shown to have higher expression of the glucose transporter GLUT4, a greater insulin‐stimulated glucose disposal rate, higher glucose oxidation rates, and higher non‐oxidative glucose metabolism compared with Type II fibers .…”
Section: Discussionmentioning
confidence: 99%
“…changes in GLUT4 expression among Type II fibers) . Thus, PA at higher intensities may be necessary to elicit the same benefits as those with higher percentage of Type I fibers . However, more research is needed to confirm this hypothesis, especially among NHBs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of obesity in African Americans and Hispanics is significantly higher than in Caucasians and Asians [50]. Black individuals have a lower maximal capacity of aerobic metabolism and greater percentage of fast contracting (type II) skeletal muscle fibers, which, together with a reduced energy consumption, predisposes them to obesity and other metabolic disorders [51]. While African Americans are particularly susceptible to obesity-related cancers, Hispanics seem to be relatively unaffected [48].…”
Section: Obesity and Chronic Inflammationmentioning
confidence: 99%
“…). Thus, even though post‐exercise vasodilatation is smaller in BA than in WE men, and even though BAs have smaller proportions of oxidative fibres (Ceaser & Hunter, ), the fall in tissue PnormalO2 during contractions at 60% MVC is apparently sufficient to allow PGs whose release is largely O 2 ‐dependent, to be released in BA men and make a substantial contribution to exercise hyperaemia.…”
Section: Evidence For and Against Pg Involvementmentioning
confidence: 99%